Molecular and MALDI-TOF MS identification of swallow bugs Cimex hirundinis (Heteroptera: Cimicidae) and endosymbionts in France - Fatima Zohra Hamlili (BMC, 2021)
Abstract Background The Cimicidae are obligatory blood-feeding ectoparasites of medical and veterinary importance. We aim in the current study to assess the ability of MALDI-TOF MS to identify Cimex hirundinis swallow bugs collected in house martin nests. Methods Swallow bugs were picked out from abandoned nests of house martin swallows and identified morphologically to the species level. The bugs were randomly selected, dissected and then subjected to MALDI-TOF MS and molecular analyses. Results A total of 65 adults and 50 nymphs were used in the attempt to determine whether this tool could identify the bug species and discriminate their developmental stages. Five adults and four nymphs of C. hirundinis specimens were molecularly identified to update our MS homemade arthropod database. BLAST analysis of COI gene sequences from these C. hirundinis revealed 98.66–99.12% identity with the corresponding sequences of C. hirundinis of the GenBank. The blind test against the database supplemented with MS reference spectra showed 100% (57/57) C. hirundinis adults and 100% (46/46) C. hirundinis nymphs were reliably identified and in agreement with morphological identification with logarithmic score values between 1.922 and 2.665. Ninety-nine percent of C. hirundinis specimens tested were positive for Wolbachia spp. The sequencing results revealed that they were identical to Wolbachia massiliensis, belonging to the new T-supergroup strain and previously isolated from C. hemipterus. Conclusions We report for the first time to our knowledge a case of human infestation by swallow bugs (C. hirundinis) in France. We also show the usefulness of MALDI-TOF MS in the rapid identification of C. hirundinis specimens and nymphs with minimal sample requirements. We phylogenetically characterized the novel Wolbachia strain (W. massiliensis) infecting C. hirundinis and compared it to other recognized Wolbachia clades. Graphical Abstract